Stabilization of Photovoltaic Systems with Fuzzy Event-Triggered Communication - Vadivel, R.; Santhosh, T. K.; Unyong, B.; Zhu, Quanxin; Cao, Jinde; Gunasekaran, Nallappan (International journal of fuzzy systems, 2023)
This article addresses the study of a photovoltaic system for type-2 interval fuzzy models via event-triggered control (ETC). Compared to similar works initiated in the references, the necessary part of modeling the ETC for the photovoltaic system ( P V ) is to produce the maximum path which should be followed to guarantee the most extreme power activity. The system models are expected to depend on uncertain parameters, which are mostly experienced in the real dynamical system. To describe the P V system with event-triggered communication delay, the behavior of a nonlinear system can be addressed by using the interval type-2 (IT2) Takagi–Sugeno (T–S) fuzzy rules with lower and upper membership functions. In this regard, we construct the suitable Lyapunov– Krasovskii functional (LKF) and integral inequalities to achieve the stability conditions and expand the maximum sampling period of the closed-loop system. The main purpose of this study is to design the event-triggered mechanism such that the resulting closed-loop system is asymptotically stable and to reduce the communication burdens of the P V system. For this, a sufficient condition is derived for the proposed system in the form of linear matrix inequalities (LMIs). Finally, simulation results are given to demonstrate the suitability and merits of the newly suggested techniques.